Exploring Quality of Primary Care for Patients Who Experience Homelessness and the Clinicians Who Serve Them: What Are Their Aspirations?. (May 2020) - Varley, Allyson L.; Montgomery, Ann Elizabeth; Steward, Jocelyn; Stringfellow, Erin; Austin, Erika L.; Gordon, Adam J.; Pollio, David; deRussy, Aerin; Hoge, April; Gelberg, Lillian; Riggs, Kevin; Kim, Theresa W.; et al.
To develop and evaluate an effective model of patient-centered, high-quality, homeless-focused primary care, our team explored key domains of primary care that may be important to patients. We anchored our conceptual framework in two reports from the Institute of Medicine (IOM) that defined components of primary care and quality of care. Using questions developed from this framework, we conducted semistructured interviews with 36 homeless-experienced individuals with past-year primary care engagement and 24 health care professionals (clinicians and researchers) who serve homeless-experienced patients in the primary care setting. Template analysis revealed factors important to this population. These included stigma, respect, and perspectives on patient control of medical decision-making in regard to both pain and addiction. For patients experiencing homelessness, the results suggest that quality primary care may have different meanings for patients and professionals, and that services should be tailored to meet homeless-specific needs.